DEVELOPING 10-11 TH GRADE STUDENTS’ LIFE SKILLS IN TEACHING ENGLISH VIA AUTHENTIC MATERIALS (Symposium on Natural and Applied Sciences, 2026)
This article investigates the pedagogical effectiveness of employing authentic materials in teaching to 10-11th grade students, with particular emphasis on the development of core life skills, including communication, critical thinking, collaboration, and problem-solving abilities. Besides, it highlights authentic materials created for real-life communicative purposes that are examined as a means of fostering meaningful language use and enhancing learners’ ability to operate in real-world contexts.
Keywords: life skills, authentic materials, English language teaching, secondary education, communicative competence, real-life contexts, collaboration, motivation.